The Language Power: A Sociolinguistic Study of Socil Status in Little Women by Greta Gerwig - Kusumawardhani, Paramita; Permata Arifin, Resti (International Journal of English and Applied Linguistics (IJEAL), 2025)
The purpose of this sociolinguistic research is to provide an in-depth analysis of language use as a reflection of power dynamics and social status in Greta Gerwig's Little Women (2019). This research uses a combination of film analysis and sociolinguistic theory to examine how language is used to communicate and influence power dynamics and social differences among the characters. Data was collected by closely observing the film, focusing on the language choices and communication strategies used by the characters. The analysis explores the complex nuances of language use in the context of social relations, examining differences in language use among different social groups, and the role of gender in shaping language patterns. The results highlight the interplay of language, power and social status in the story of the film "Little Women", providing valuable insights into the field of sociolinguistics and highlighting the importance of language in describing and challenging social dynamics. The analysis focuses on language use in the context of social relations, including language use by characters from different social groups and differences in language use between male and female characters. The research provides insights into the relationship between language, power, and social status in the context of film and makes a contribution to sociolinguistics.